2022
DOI: 10.21037/atm-22-3227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fecal microbiota transplantation on the TGF-β1/Smad signaling pathway in rats with TNBS-induced colitis

Abstract: Background Traditional treatments for inflammatory bowel disease (IBD) have adverse side effects, and patients who receive such treatments have high recurrence rates. Fecal microbiota transplantation (FMT) has become an increasingly popular therapeutic option for patients with IBD. However, the mechanism by which FMT alleviates this disease remains unclear. Methods In this study, a rat model of 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis was established an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
1
2
0
1
Order By: Relevance
“…Furthermore, we found an elevated level of TGF-β cytokine in TNBS-treated groups compared to controls. In accordance with our results, Qui et al [ 39 ] showed that TNBS treatment significantly elevated TGF-β expression in rats, and Del Zotto et al [ 40 ] found the same alteration in the colonic tissue of IBD patients. Furthermore, Silva et al [ 41 ] found that chronic exercise significantly attenuated TGF-β levels in middle-aged obese mice.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found an elevated level of TGF-β cytokine in TNBS-treated groups compared to controls. In accordance with our results, Qui et al [ 39 ] showed that TNBS treatment significantly elevated TGF-β expression in rats, and Del Zotto et al [ 40 ] found the same alteration in the colonic tissue of IBD patients. Furthermore, Silva et al [ 41 ] found that chronic exercise significantly attenuated TGF-β levels in middle-aged obese mice.…”
Section: Discussionsupporting
confidence: 93%
“…Among experimental studies focused on gastrointestinal diseases found in the literature, IIRI-and 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats appears as a current model used by many authors and research groups around the world. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For this reason, we selected these two relevant pathologies to evaluate the experimental BK procedure in an intestinal injury scenario. IIRI was used for simulating a model of intestinal intussusception, strangulated hernia or intestinal transplantation.…”
Section: Step 2 Bk Model Applicationmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The same situation occurs in the field of experimental colitis, where old and recent scientific articles use one animal in each LI sample collection. [30][31][32][33][34][35][36][37] For the reasons mentioned above, it is a challenge to develop models that enable reducing the number of animals involved in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Este es un modelo experimental de interés de investigación en la actualidad entre las patología de intestino grueso utilizado por múltiples autores y grupos de investigación. (104)(105)(106)(107)(108)(109)(110)(111) Materiales y métodos: Se constituyeron tres grupos compuestos por ratas Sprague-Dawley hembras (peso 190 ± 2,6 gr). A las cuales se les realizó la técnica de BK en la porción distal del intestino grueso.…”
Section: Bk En Un Modelo De Colitis Inducido Por Tnbsunclassified